Interferon priming enables cells to partially overturn the SARS coronavirus-induced block in innate immune activation - Kuri, Thomas; Zhang, Xiaonan; Habjan, Matthias; Martínez-Sobrido, Luis; García-Sastre, Adolfo; Yuan, Zhenghong; Weber, Friedemann (Journal of General Virology, 2009)
SARS coronavirus (SARS-CoV) is known to efficiently suppress the induction of antiviral type I interferons (IFN-α/β) in non-lymphatic cells through inhibition of the transcription factor IRF-3. Plasmacytoid dendritic cells, in contrast, respond to infection with production of high levels of IFNs. Here, we show that pretreatment of non-lymphatic cells with small amounts of IFN-α (IFN priming) partially overturns the block in IFN induction imposed by SARS-CoV. IFN priming combined with SARS-CoV infection substantially induced genes for IFN induction, IFN signalling, antiviral effector proteins, ubiquitination and ISGylation, antigen presentation and other cytokines and chemokines, whereas each individual treatment had no major effect. Curiously, however, despite this typical IFN response, neither IRF-3 nor IRF-7 was transported to the nucleus as a sign of activation. Taken together, our results suggest that (i) IFN, as it is produced by plasmacytoid dendritic cells, could enable tissue cells to launch a host response to SARS-CoV, (ii) IRF-3 and IRF-7 may be active at subdetectable levels, and (iii) SARS-CoV does not activate IRF-7.